Education and Technology: The Combined Effect on Performance of SMEs Through Accounting Applications - Putra Aditya Pratama, Devangga; Aini Anisa, Nur; Mulyani, Mulyani; Arifin, Syamsul; Darti Megasari, Aisyah; Liftiana, Rika (Economic and Bussiness Faculty, Dr Soetomo University, 2025)
. This study aims to determine how much influence the level of education and use of UKM accounting applications on the performance of UMKM. Data collection uses the method of distributing questionnaires directly to each UMKM respondent. In determining the population in this study is the level of education and use of UKM accounting applications in Madiun Regency. While in taking the sample using purposive sampling technique. The respondents were 60 UMKM who had met the previously determined answer criteria. In terms of data processing, the author uses the SPSS Statistics program version 26.0 for windows. The results of this study can be concluded that based on the t-test of the education level variable (X1), the t-count value is 3.456 with a sig value. of 0.001 less than 0.05 (0.001 <0.05) means that the level of education affects the performance of UMKM in the Madiun Regency area. The use of the UKM accounting application (X2) obtained a t value of 3.669 with a sig value. of 0.001 means that the use of UKM accounting applications has an effect on the performance of UMKM in the Madiun Regency area. Thus the results of this study state that the hypothesis is accepted